Unusual "Subcutaneous Mass" in a Young Adult: A Case Report of Sclerosing Epitrochlear Lymph Node and Brief Review of the Literature - Ding, MD, PhD, Liang; Khazaeli, MD, Mahyar; Lin, MD, PhD*, Lin (North American Journal of Medicine and Science, 2022)
Lymph nodes are specialized tissues that play an essential role in the immune system. Nodal hyalinization/sclerosis is often seen in the elderly, involving the mediastinum, pelvis, and other areas. Hyalinization of the lymph node might contribute to impaired filtration function of the node. Nevertheless, the clinical significance is still unclear. Here, we report a 35-year-old Caucasian female with an unremarkable past medical history, presented at the dermatology clinic with a subcutaneous mass in the forearm, and an excisional biopsy was performed. The histological findings are consistent with a lymph node with hyalinization and storiform sclerosis. The patient is doing well after the focal excision. Although deposition of hyaline material can be seen in the pelvic and inguinal lymph nodes of the elder, its histology is drastically different from the one seen in our case. In this case report and brief review, we compare and summarize several benign and malignant conditions associated with nodal hyalinization with or without a storiform pattern [N A J Med Sci. 2022;15(1):001-007. DOI: 10.7156/najms.2022.1501001] Key Words: lymph node, hyalinization, sclerosis, storiform pattern